Obstetric anal sphincter injuries (OASIS): using transperineal ultrasound (TPUS) for detecting, visualizing and monitoring the healing process - Anna-Lena Stickelmann; Lieven Nils Kennes; Miriam Hölscher; Charlotte Graef; Tomas Kupec; Julia Wittenborn; Elmar Stickeler; Laila Najjari (BMC, 2022)
Abstract Purpose The aim of this study was to examine whether OASIS, and its extent, can be confirmed or excluded using transperineal ultrasound (TPUS). A further objective of this study was to monitor the healing process over a period of 6 months and to establish a connection between the sonographic appearance of obstetric anal sphincter injury (OASIS) and anal incontinence. Materials and methods In this retrospective clinical study, women with OASIS who gave birth between March 2014 and August 2019 were enrolled. All the patients underwent TPUS 3 days and 6 months after delivery. A GE E8 Voluson ultrasound system with a 3.5-5 MHz ultrasound probe was used. The ultrasound images showed a third-degree injury, with the measurement of the width of the tear and its extent (superficial, partial, complete, EAS and IAS involvement). A positive contraction effect, a sign of sufficient contraction, was documented. Six months after delivery, a sonographic assessment of the healing (healed, scar or still fully present) was performed. A Wexner score was obtained from each patient. The patients' medical histories, including age, parity, episiotomy and child's weight, were added. Results Thirty-one of the 55 recruited patients were included in the statistical evaluation. Three patients were excluded from the statistical evaluation because OASIS was excluded on TPUS 3 days after delivery. One patient underwent revision surgery for anal incontinence and an inadequately repaired anal sphincter injury, as shown sonographic assessment, 9 days after delivery. Twenty patients were excluded for other reasons. The results suggest that a tear that appears smaller (in mm) after 3 days implies better healing after 6 months. This effect was statistically significant, with a significance level of alpha = 5% (p = 0.0328). Regarding anal incontinence, women who received an episiotomy had fewer anal incontinence symptoms after 6 months. The effect of episiotomy was statistically significant, with a significance level of alpha = 5% (p = 0.0367). Conclusion TPUS is an accessible, non-invasive method for detecting, quantifying, following-up and monitoring OASIS in patients with third-degree perineal tears. The width, as obtained by sonography, is important with regard to the healing of OASIS. A mediolateral episiotomy seems to prevent anal incontinence after 6 months.